Stretch-activated cation channel from larval bullfrog skin - Hillyard, Stanley D. (Company of Biologists, 2010)
Cell-attached patches from isolated epithelial cells from larval bullfrog skin revealed a cation channel that was activated by applying suction (−1 kPa to −4.5 kPa) to the pipette. Activation was characterized by an initial large current spike that rapidly attenuated to a stable value and showed a variable pattern of opening and closing with continuing suction. Current–voltage plots demonstrated linear or inward rectification and single channel conductances of 44–56 pS with NaCl or KCl Ringer's solution as the pipette solution, and a reversal potential (−V(p)) of 20–40 mV. The conductance was markedly reduced with N-methyl-D-glucamide (NMDG)-Cl Ringer's solution in the pipette. Neither amiloride nor ATP, which are known to stimulate an apical cation channel in Ussing chamber preparations of larval frog skin, produced channel activation nor did these compounds affect the response to suction. Stretch activation was not affected by varying the pipette concentrations of Ca(2+) between 0 mmol l(−1) and 4 mmol l(−1) or by varying pH between 6.8 and 8.0. However, conductance was reduced with 4 mmol l(−1) Ca(2+). Western blot analysis of membrane homogenates from larval bullfrog and larval toad skin identified proteins that were immunoreactive with mammalian TRPC1 and TRPC5 (TRPC, canonical transient receptor potential channel) antibodies while homogenates of skin from newly metamorphosed bullfrogs were positive for TRPC1 and TRPC3/6/7 antibodies. The electrophysiological response of larval bullfrog skin resembles that of a stretch-activated cation channel characterized in Xenopus oocytes and proposed to be TRPC1. These results indicate this channel persists in all life stages of anurans and that TRP isoforms may be important for sensory functions of their skin.